2008
DOI: 10.1086/587646
|View full text |Cite
|
Sign up to set email alerts
|

Maternal‐Fetal DNA Admixture Is Associated with Intrapartum Mother‐to‐Child Transmission of HIV‐1 in Blantyre, Malawi

Abstract: Intrapartum MTCT was associated with placental microtransfusions. The associations among placental microtransfusion, in-utero MTCT, maternal immunosuppression, and poor birth outcome should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
(17 reference statements)
1
16
1
Order By: Relevance
“…The observed contrast in cytokine levels between in utero and intrapartum MTCT provides additional data to support the hypothesis that IU and IP MTCT have different molecular mechanisms. Consistent with this hypothesis, we (and others) have previously observed no association between maternal-fetal blood admixture (also called placental microtransfusions) and IU MTCT [52-54]; in contrast, using two different assays, we have observed an association between placental microtransfusions and IP MTCT [52, 53]. Whether or not the prevalent edema that was associated with intrapartum MTCT is related to placental microtransfusions cannot be determined from this study.…”
Section: Discussionsupporting
confidence: 80%
“…The observed contrast in cytokine levels between in utero and intrapartum MTCT provides additional data to support the hypothesis that IU and IP MTCT have different molecular mechanisms. Consistent with this hypothesis, we (and others) have previously observed no association between maternal-fetal blood admixture (also called placental microtransfusions) and IU MTCT [52-54]; in contrast, using two different assays, we have observed an association between placental microtransfusions and IP MTCT [52, 53]. Whether or not the prevalent edema that was associated with intrapartum MTCT is related to placental microtransfusions cannot be determined from this study.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies from the MHP cohort have reported an association between malaria and the HIV-1 load (53), an association between maternal syphilis seroreactivity and HIV-1 MTCT (52), an association between maternal-infant blood admixture during intrapartum HIV-1 MTCT (40,41), and a reduction in HIV-1 quasispecies diversity during HIV-1 MTCT (42). In order to better understand the relationship between the HIV-1 load in peripheral and placental plasmas, we stratified viral-load data from the MHP cohort by HIV-1 transmission status.…”
Section: Resultsmentioning
confidence: 99%
“…It is currently unknown if alterations in these Env positions allow HIV-1 to escape other antibody-directed immune reactions, such as antibody-dependent cellular cytotoxicity (ADCC). In addition to selective pressure from the immune system, the differences in env associated with either placental localization or in utero MTCT could also be a result of viral adaptation to the tissues of the placenta, which has a unique repertoire of (40,41,46). Thus, our working assumption is that HIV-1 must cross an intact maternal-fetal barrier during in utero MTCT.…”
Section: Discussionmentioning
confidence: 99%
“…Our study failed to support this hypothesis despite finding a high frequency of detectible maternal DNA in cord blood. However, Kwiek et al 21 , working independently in Malawi, recently reported a correlation between maternal DNA in cord blood and perinatal HIV transmission risk. Their report was based on data from 9 infected and 69 uninfected infants, but despite small numbers, they observed significant associations between levels of detected maternal DNA in umbilical cord blood and intrapartum HIV transmission (p=0.02), as well as a surprising possible association with in utero transmission (13 infected infants, p=0.06).…”
Section: Discussionmentioning
confidence: 99%